ANALYSIS OF THE VISION STATEMENT OF THE FASTEST GROWING TECHNOLOGY COMPANIES IN TURKEY - Aslan, Fethi; Uzun, Hasan (My University, 2021)
The vision is the expression of where the business wants to be in the future. A forceful vision has a significant impact on business decisions, such as mission and strategy. The most important component of a business's vision is the vision statement. A vision statement is successfully defined only when it is developed based on a set of fundamental criteria. This study has been prepared to quantitatively evaluate whether businesses can define a successful vision statement. For this purpose, a quantitative evaluation method has been developed. The developed method was used to evaluate the vision statements of the fastest growing technology companies in Turkey. Different methods and approaches were used to develop the method used in the study. In this context, first of all, the criteria and approaches used in the literature for the creation of the vision statement were examined. Examined criteria and approaches have been transformed into common criteria that will enable the evaluation of vision statement by thematic analysis method. Afterwards, heuristic evaluation method was used to identify the experts required to evaluate within the framework of common criteria. At the last stage, experts in the fields of strategy, management, planning, control and technology evaluated the vision statements of the fastest growing technology enterprises according to the determined criteria. In order to measure the numerical meaning of these evaluations, the visual acuity score approach of the eye was used and the vision intelligence score formula was developed. The calculated vision intelligence score enabled the evaluation and comparative analysis of the vision statements of the enterprises. This method has made an important contribution to the literature due to its role in facilitating the analysis of vision statements containing subjective judgments with an objective evaluation framework and the creation of an effective vision statement.
Keywords: Vision; Vision Intelligence; Thematic Analysis; Eye-Vision-Organization Relationship; Heuristic Evaluation